Syntheses and biological properties of benzo[4',5'] imidazo[2',1': 6,1] pyrido[2,3-d]pyrimidines: mini-review - Harutyunyan, A. A. (ՀՀ ԳԱԱ հրատ.)
The known methods for the synthesis of benzo[4',5']imidazo[2',1': 6,1] pyrido[2,3-d]pyrimidine heterocyclic derivatives based on heterocyclic reactions of substituted benzimidazoles and alternative approaches using substituted pyrimidinyl-5-propanoic acids have been considered.Դիտարկվել են հետերոցիկլիկ համակարգի՝ բենզո[4′,5′] իմիդազո[2′,1′:6,1]պիրիդո-[2,3-d] պիրիմիդինի սինթեզի հայտնի մեթոդներ, հիմնված տեղակալված բենզիմիդազոլի հետերոցիկլման և այլընտրանքային մոտեցումներ տեղակալված պիրիմիդինիլ-5-պրոպանաթթվի կիրառման վրա: Рассмотрены известные методы синтеза производных гетероциклической системы бензо[4′,5′]имидазо[2′,1′:6,1] пиридо[2,3-d]пиримидина, основанные на реакциях гетероциклизации замещенных бензимидазолов и альтернативные подхо-ды с использованием замещенных пиримидинил-5-пропановых кислот.
Keywords: Քիմիա